Umbilical Cord MSC-Secretome Therapy Enhances Erectile Function in Elderly Men - Digambiro, Reza Aditya; Fiji, Wijaya Taufik; Ilona, florinda; Chendrasari, Julian (UMI Medical Journal, 2025)
Background: Reduced erectile capacity often appears as part of physiological shifts during aging potentially implicating broader physiological or social realms. These declines originate from intricate underlying conditions: endothelial dysfunction, unstable hormonal patterns, compromised vascular structures, oxidative stress escalations, and inflammatory cascades. Recently, attention has drifted towards secretome derived from umbilical cord mesenchymal stem cells (UCMSC)—an eclectic blend of cytokines, extracellular vesicles, and growth factors—suggesting foundational regenerative qualities surpassing conventional symptomatic therapies, like phosphodiesterase-5 inhibitors (PDE-5i). Methods: In this study, ederly male participants (n=64, aged ≥60) diagnosed with erectile dysfunction (ED) received intracavernosal UCMSC-secretome injections every two weeks for three sessions. No control group was included; efficacy was tracked through pre- and post-intervention evaluations using the International Index of Erectile Function (IIEF-5). Results: A statistically notable improvement emerged—average IIEF-5 scores increasing by about 5.49 points (p<0.001; Cohen’s d=1.99). With the satisfaction averaging approximately 8.03/10. Conclusion: Extensive, randomized controlled trials could more conclusively elucidate the genuine potential of secretome interventions.